Worker Safety in Maine’s Boatyards: Improving OSHA Compliance Efforts - Pare, Jeremy (Maine Policy Review, 2020)
According to the Occupational Safety and Health Administration (OSHA), Maine’s boatyards are a high-hazard industry, given the many potential threats their employees face daily. Maine’s boatyards struggle with OSHA regulations because OSHA’s command-and-control rules leave little room for flexibility, and as evidenced by the boatyards’ high workers’ compensation costs and injury rates, implementation does not effectively protect boatyard workers. This article investigates whether changes to OSHA’s 50-year-old punitive regulatory strategy can influence the way boatyards self-regulate and decrease hazards and minimize the risk of injury to workers. Through focus groups and interviews, the article provides evidence that changes within OSHA’s regulatory strategy are necessary to decrease the hazards present in Maine boatyards. Suggested changes include site-specific injury and illness prevention programs and more frequent inspections with opportunities for boatyards to fix issues. These improvements should increase cooperative efforts between OSHA, the state of Maine, and Maine’s boatyards and reduce the number of worker injuries.